A legal study on social-ills committed amongst the foreign domestic workers / Muhammad Adhwa 'Azfar Muhammad Tajuddin…[et al.] - Muhammad Tajuddin, Muhammad Adhwa 'Azfar; Halimi, Haidar Ayumi; Sam Abd Mutalib, Norain Solehah; Tengku Razali, Tengku Nuraishah; Tuan Roslan, Tg Syazwany Yasmyn (2010)
This research aims to review the existing law in controlling the entry and departure of the foreign domestic workers and analyze the application of the law in terms of efficiency to prevent and curb social ills among the foreign domestic workers. The law dealing with the said matter is spelt under the Immigration Act 1959 and the Employment Act 1955. The study emphasizes on the area of administration of the recmitment of foreign domestic workers in Malaysia. In particular, the lack of enforcement by the Immigration Department in exercising the procedures and regulations which has been standardized in the Immigration Act 1959 will be highlighted. Furthermore, the lacunas of certain important rules in the Employment Act 1955 will also be mentioned. Hence, it is hereby opined that the Immigration Act together with relevant authorities such as the Royal Malaysian Police and the Home Ministry should be more efficient in terms of their enforcement in this matter. Furthermore, the role of the Employment Act 1955 should be wider and the legislation should consider revising the said Act. This is provital for the prevention of social ills committed by foreign workers which would ultimately make Malaysia a crime safe society.